Hospital Survey on Patient Safety Culture: psychometric evaluation in Kuwaiti public healthcare settings - Al Salem, Gheed (BMJ Open, 2019)
OBJECTIVE: As healthcare organisations endeavour to improve the quality and safety of their services, there is increasing recognition of the importance of building a culture of safety to promote patient safety and improve the outcomes of patient care. Surveys of safety culture/climate have not knowingly been conducted in Kuwait public hospitals, nor are valid or reliable survey instruments available for this context. This study aims to investigate the psychometric properties of the HSOPSC (Hospital Survey on Patient Safety Culture) tool in Kuwaiti public hospitals in addition to constructing an optimal model to assess the level of safety climate in this setting. DESIGN: Cross-sectional study. SETTING: Three public hospitals in Kuwait. PARTICIPANTS: About 1317 healthcare professionals. MAIN OUTCOME MEASURE: An adapted and contextualised version of HSOPSC was used to conduct psychometric evaluation including exploratory factor analysis, confirmatory factor analysis reliability and correlation analysis. RESULTS: 1317 questionnaires (87%) were returned. Psychometric evaluation, showed an optimal model of eight factors and 22 safety climate items. All items have strong factor loadings (0.42–0.86) and are theoretically related. Reliability analysis showed satisfactory results (α >0.60). CONCLUSIONS: This is the first validation study of a standardised safety climate measure in a Kuwaiti healthcare setting. An optimal model for assessing patient safety climate was produced that mirrors other international studies and which can be used for measuring the prevailing safety climate. More importance should be attached to the psychometric fidelity of safety climate questionnaires before extending their use in other healthcare culture and contexts internationally.